THE ROLE OF THE SECURITY MANAGEMENT IN PREVENTING MISUSE OF VIRTUAL CURRENCIES IN THE MONEY LAUNDERING PROCESS AND THE FINANCING OF TERRORISM - Mirković, Vladan M (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Technological development related to virtual currencies, intensity and frequency of transaction and expansion of virtual markets stands on opposite side in comparison with their legal status in international and domestic law. Such discrepancy produces ideal environment for money laundering and financing terrorism and other forms of illegal acts because security management doesn’t have appropriate legal and political framework for organizing and planning measures which are aimed to prevent the misuse of virtual currencies in money laundering process. In positive law of the Republic of Serbia virtual currencies are mentioned in Law on the preventing of money laundering and the financing of terrorism, but only as obligation for actors which are involved in virtual currencies transactions to act as the Law prescribes it. Virtual currencies and problems related to them have not been mentioned in other documents on strategic level of management. Subsequently, this situation on strategic level produces several problems on coordinating and operational level. As an overall result of lack of legal regulations on virtual currencies, obliged entities don’t have obligation to acquire license or to register at the National bank of Serbia as entities which trade virtual currencies, virtual currencies are treated as any other costume and bank and other financial institutions which are obliged under the Law to create and shape their politics toward virtual currencies based on their assessment of threat. This can cause serious problems because financial entities which are engaged in this type of transactions are in the first line of battle for preventing money laundering. Similar objection could be placed for state representatives because public interest which could be here at stake is their responsibility. In order to enhance potential for preventing from the misuse of virtual currencies in money laundering process several suggestions are given in this paper.